Pre-Service EFL Teachers’ Perceptions of Formative Assessment Literacy in Indonesian - Andri Suherman; M. Adib Nazri; Ari Prasetyaningrum; Yulia Agustina (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
The current study investigates the formative assessment literacy of Indonesian pre-service English teachers by adopting a sequential mixed-method approach. The survey data revealed that participants had a moderate level of formative assessment literacy (M = 3.02), with varying scores across three components. The conceptual domain scored the highest (M = 3.12), followed by the socio-emotional domain (M = 2.98) and the practical domain (M = 2.96). The second finding gained from the second part of the survey and from interview sessions indicated five different challenges encountered by the participants in practicing formative assessment. The issues raised by the participants were related to limited support from their institution, their heavy teaching workload, lack of digital literacy, their students’ low learning motivation, and the participants’ inadequate assessment skills and knowledge. Although this study has several limitations, it provides several implications, such as the urgency of providing training for teachers to help them improve their assessment literacy.